The Efffect of Wave Sound at Frequency 3 kHz - 4 kHz on Logawa Rice Resistance to Rice Lices - Kuni Nadliroh (Natural B, Journal of Health and Environmental Sciences, 2018)
Rice lice is one type of pest that attacks rice, the presence of rice lice can damage the content of rice, rice form and color of rice. Rice that is exposed to rice lice pests will easily fragile and turn into powder and the color of the rice turns yellowish. Innovation is needed to reduce the population of rice lice in the storage phase, so this study aims to determine the effect of sound waves of 3 KHz to 4 KHz frequency on the resistance of logawa varieties to rice lice, in this study the rice plants given the treatment of sound waves of 3 KHz frequency until 4 KHz and without sound waves as controls. Giving of sound waves is done every day from 06.00 to 09.00.